ANALISIS HUBUNGAN IPM DAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI SUMATERA UTARA - Muhammad Garibaldi; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2014)
The purpose of this research is to know term relation of human developmentindex (HDI) and economic growth regency/city in north of sumatera provinceduring the period 2004-2012.This research uses panel data, with method klassen typology to see benefitof regional, and cointegration test for to see long term relationship beetwen Humandevelopment index and growth of economic by using eviews programe 6.The result showed that by using klassen typology is 1 regency and 4 city forcategory quadrant I. meanwhile 8 regency and 1 city in quadrant II. And then 4regency and 2 city category in quadrant III. And also 12 regency and 1 citycategory in quadrant 4. From result of cointegration test showed a long termequilibrium relationship beetween Human development index and economic growth.